Cost analysis of the surgical treatment of fractures of the proximal humerus: an evaluation of the determinants of cost and comparison of the institutional cost of treatment with the national tariff - Sabharwal,S; Carter,AW; Rashid,A; Darzi,A; Reilly,P; Gupte,CM (Bone & Joint Journal, 2016)
Aims The aims of this study were to estimate the cost of surgical treatment of fractures of the proximal humerus using a micro-costing methodology, contrast this cost with the national reimbursement tariff and establish the major determinants of cost.Methods A detailed inpatient treatment pathway was constructed using semi-structured interviews with 32 members of hospital staff. Its content validity was established through a Delphi panel evaluation. Costs were calculated using time-driven activity-based costing (TDABC) and sensitivity analysis was performed to evaluate the determinants of costResults The mean cost of the different surgical treatments was estimated to be £3282. Although this represented a profit of £1138 against the national tariff, hemiarthroplasty as a treatment choice resulted in a net loss of £952. Choice of implant and theatre staffing were the largest cost drivers. Operating theatre delays of more than one hour resulted in a loss of incomeDiscussion Our findings indicate that the national tariff does not accurately represent the cost of treatment for this condition. Effective use of the operating theatre and implant discounting are likely to be more effective cost containment approaches than control of bed-day costs.Take home message: This cost analysis of fractures of the proximal humerus reinforces the limitations of the national tariff within the English National Health Service, and underlines the importance of effective use of the operating theatre, as well as appropriate implant procurement where controlling costs of treatment is concerned.